A Tax Guide for Artists and Arts Organizations (Book). - Crumbley, D. Larry; Burns, Thomas J. (The Accounting Review, 1980)
Abstract Reviews the book "A Tax Guide for Artists and Arts Organizations," edited by Herrick K. Lidstone.